Optimizing Project-Based Mahārah al-Istimāʿ Learning among Arabic Language Education Students at Universitas Negeri Makassar - Lailaa, Hikmatul (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
This study aims to optimize the development of listening skills through the implementation of the Project-Based Learning (PBL) model among students in the Arabic Language Education Program. This study employs a Classroom Action Research (CAR) approach based on Kurt Lewin’s model, which includes the stages of planning, action, observation, and reflection, conducted over two cycles. The research subjects consisted of 29 students. Data collection techniques included tests, observations, and documentation. The results showed that the implementation of project-based learning significantly improved students’ listening skills. This was evidenced by an increase in the average score from 47.86 in the pre-cycle phase to 68.31 in Cycle I, and further to 84.97 in Cycle II. The percentage of learning achievement also increased from 20.69% in the pre-cycle to 65.52% in Cycle I, and reached 96.55% in Cycle II. Additionally, project-based learning enhanced students’ engagement, participation, as well as their critical and collaborative thinking skills during the learning process. Thus, the Project-Based Learning model has proven effective in optimizing the acquisition of listening skills and creating a more interactive, contextual, and student-centered learning experience.